Numerical study of the impact of stress concentration on shale gas production - Peng, Yan; Wang, Xiaohan; Sheng, Liji (Frontiers in Earth Science, 2024)
It is of great significance to predict production for exploitation of oil and gas resources. The flowgeomechanical coupling effect has an important role in predicting production. Shale rocks and the stress-dependent permeability model is critical to represent this coupling effect. The pore network of shale rock is not abundant like the one of coal rock. The matrix blocks of shale rock are not completely separated by pore network. There is a stress concentration around pore when shale rock deforms. Based on previous studies, in this paper, the stress-dependent permeability model considering impact of stress concentration is used to build a flow-geomechanical coupling numerical simulation model for shale gas reservoir. This coupling numerical simulation model is validated by field data. Sensitivity studies are conducted to discuss the difference of production prediction between the new model and the common model. The main conclusions include:(1) The new model can well fit the field data and experimental data. The average error of daily production rate between numerical solution and field data is 8%. It indicates that this new model can be used to predict shale gas production. (2) Under the geomechanical condition of real reservoir, the difference of predicted production between model with or without stress concentration can be huge and increases with the ratio of a to b. If this ratio is less than 50, the impact of stress concentration is not significant. Otherwise, the impact of stress concentration on production increases sharply and can exceed 20%. (3) The adsorption-induced strain enhances the impact of stress concentration on production. When the Langmuir pressure exceeds 1MPa and Langmuir strain exceeds 0.01, the impact magnitude of stress concentration can exceed 10%.